2015
DOI: 10.1155/2015/316863
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Concurrent MPO-/PR3-Negative ANCA-Associated Glomerulonephritis and Membranous Glomerulopathy

Abstract: We report a case in which antineutrophil cytoplasmic antibody- (ANCA-) associated glomerulonephritis and membranous glomerulopathy (MGN) were detected concurrently. The patient showed rapidly progressive renal deterioration. A renal biopsy showed crescentic glomerulonephritis, together with marked thickening and spike and bubbling formations in the glomerular basement membranes. Indirect immunofluorescence examination of the patient's neutrophils showed a perinuclear pattern. Enzyme-linked immunosorbent assays… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
2
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
0
2
0
3
Order By: Relevance
“…Only a few of these autoantibodies, such as ANCAs, are currently used in routine practice in the diagnosis of patients with small-vessel vasculitis [ 8 ]. Moreover, in addition to MPO and PR3, other antigens can lead to the production of autoantibodies [ 19 ]. Based on this background, we aimed to test the total circulating ANCAs and we observed that patients with a SARS-CoV-2 infection had serum levels of ANCAs that were significantly higher than the control subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only a few of these autoantibodies, such as ANCAs, are currently used in routine practice in the diagnosis of patients with small-vessel vasculitis [ 8 ]. Moreover, in addition to MPO and PR3, other antigens can lead to the production of autoantibodies [ 19 ]. Based on this background, we aimed to test the total circulating ANCAs and we observed that patients with a SARS-CoV-2 infection had serum levels of ANCAs that were significantly higher than the control subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the increase in the ANCAs in the patients of the second wave remains unexplained. This finding could be explained by the release of other antigens that can lead to ANCA production [ 19 ]. Furthermore, another explanation might be the formation of neutrophil extracellular traps in which neutrophils kill pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…Se ha demostrado que la infusión de éstas no da lugar al desarrollo de glomerulonefritis en modelos animales. Con base en estos hallazgos, se ha propuesto que los ANCA no causan daño glomerular en forma directa, sino que los neutrófilos que ellos activan son los que producen los cambios histopatológicos ya descriptos mediante la liberación de agentes inflamatorios y proteínas de degradación, causantes del daño glomerular y la proliferación celular 5 .…”
Section: Discusión Y Conclusionesunclassified
“…Algunas investigaciones realizadas en Francia, Reino Unido, España y China se enfocaron en el estudio comparativo de dos grupos de pacientes: GNRP de tipo III positiva y negativa a ANCA. Dos de estos estudios, uno conducido en Pekín de Min Chen, et al 6 y otro realizado en España de Villacorta, et al 7 concluyeron que la población de pacientes con GNRP de tipo III negativa a ANCA es significativamente más joven al momento del diagnóstico, en comparación con la población de pacientes con GNRP de tipo III positiva a ANCA, tal y como se observó en el caso clínico presentado 5,6 .…”
Section: Discusión Y Conclusionesunclassified
See 1 more Smart Citation